A FACTORIAL DESIGN APPLIED TO THE STUDY OF CHROMIUM TOXICITY ON THE GLUTATHIONE LEVELS OF Brachiaria brizantha AND Brachiaria ruziziensis SEEDLINGS - Rafael Marques; Marcone A. L. de Oliveira; Cassia R. G. dos Reis; Maurício M. Köpp; Leônidas P. Passos (Química Nova, 2015)
Chromium toxicity affects redox reactions within plant cells, generating detrimental reactive oxygen species. Glutathione is an antioxidant peptide and also a substrate for the production of phytochelatins, which are chelating peptides reported to mitigate Cr3+ toxicity in plants. In this study, Brachiaria brizantha (B. brizantha) and Brachiaria ruziziensis (B. ruziziensis) seedlings were evaluated for physiological responses and glutathione production following the addition of zero or 5 mg L-1 Cr3+ to the nutrient solution. Glutathione levels were determined by colorimetric analysis at 412 nm using 5,5'-dithio-bis(2-nitrobenzoic acid) as a chromophore reagent and recovery with glutathione reductase (with evaluations at days 10 and 20 of continuous growth). The assessments were carried out in a completely randomized design with 2 authentic replications, and arranged in a 23 factorial. Cr3+ caused an average increase of 0.76 mg g-1 in the initial glutathione content. However, by day 20 there was an average reduction of 3.63 mg g-1. Chromium-affected physiological detrimental responses, albeit detected in both species, were less-pronounced in B. ruziziensis, along with a much higher level of glutathione. This study indicates that B. ruziziensis has a greater tolerance for chromium toxicity than B. brizantha, and that glutathione is likely to be involved in the mitigation of chromium stress in B. ruziziensis.